Do Federal Regulations Affect Gender, Racial, and Ethnic Disparities in Chronic Rhinosinusitis Research?. (June 2022) - Spielman, Daniel B.; Schlosser, Rodney J.; Liebowitz, Andi; Sharma, Rahul; Overdevest, Jonathan; Mattos, Jose; Gudis, David A.
Objective: The Food and Drug Administration and the National Institutes of Health (NIH) have asserted that diverse demographic representation in clinical trials is essential. In light of these federal guidelines, the objective of this study is to assess the racial, ethnic, and gender demographics of patients enrolled in clinical trials registered with the NIH that evaluate chronic rhinosinusitis with nasal polyposis (CRSwNP) relative to the demographics of the US population. Study Design: Cross-sectional study. Setting: Not applicable. Methods: ClinicalTrials.gov was queried to identify all prospective clinical trials for CRSwNP. Individual study and pooled data were compared with national US census data. Results: Eighteen studies were included comprising 4125 patients and evaluating dupilumab, mepolizumab, omalizumab, fluticasone/OptiNose, MediHoney, mometasone, and SINUVA. Women constituted 42.7% of clinical trial participants. Of the 4125 participants, 69.6% identified as White, 6.6% as Black, 20.8% as Asian, 0.1% as Pacific Islander, 0.4% as American Indian, 8.0% as Hispanic, and 2.4% as other. The racial, ethnic, and gender composition of the pooled study population differs significantly from national US census data, with underrepresentation of Black, Hispanic, Pacific Island, and American Indian individuals, as well as females ( P < .05). Conclusion: The racial, ethnic, and gender demographics of patients enrolled in CRSwNP clinical trials registered with the NIH differ significantly from the demographics of the US population, despite federal guidelines advising demographically representative participation. Proactive efforts to enroll participants that better represent anticipated treatment populations should be emphasized by researchers, institutions, and editorial boards.